2001
DOI: 10.1111/j.1572-0241.2001.03951.x
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal motor patterns in critically ill patients after major abdominal surgery

Abstract: Small intestinal pressure wave bursts are seen immediately after elective aortic aneurysm repair, but the migration of these bursts is frequently abnormal for phase III interdigestive activity. Duodenal nutrient delivery did not interrupt the occurrence of these bursts. Persistence of pressure wave bursts in this setting may be important in the delivery of enteral nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…The results from the current study support the hypothesis that an abnormal patterning of small intestinal motor activity may also contribute to impaired nutrient absorption in the critically ill. Similar motor patterns are seen during critical illness (6,38), at which time postprandial motility is disrupted by bursts of activity that resemble phase III of the MMC. Further direct studies examining the potential impact of changes in motor activity on nutrient absorption in critically ill patients are thus required.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The results from the current study support the hypothesis that an abnormal patterning of small intestinal motor activity may also contribute to impaired nutrient absorption in the critically ill. Similar motor patterns are seen during critical illness (6,38), at which time postprandial motility is disrupted by bursts of activity that resemble phase III of the MMC. Further direct studies examining the potential impact of changes in motor activity on nutrient absorption in critically ill patients are thus required.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, small intestinal motility is frequently disturbed during critical illness. Migrating bursts of activity resembling phase III of the interdigestive MMC persist during enteral feeding, indicating a failure of conversion to the postprandial motor pattern (6,38). The potential impact of this abnormality on nutrient transit and absorption has not previously been assessed.…”
mentioning
confidence: 99%
“…However, the migration of these bursts was frequently abnormal. 23 Miedema et al also showed that although jejunal motor activity was present within 6 hours of elective AAA surgery, it was nonpropulsive, the motility index was reduced and was associated with significant abnormalities in the migratory motor complex. 24 It has been suggested that the retroperitoneal approach may lead to better recovery and quicker return of normal bowel function after aortic surgery.…”
Section: Discussionmentioning
confidence: 96%
“…We did not take defecation as parameter as it may simply reflect colonic emptying and not necessarily the return of bowel movements [8] . Feeding may actually be helpful in enhancing return of post operative bowel function by stimulating bowel motility [9] . Food intake stimulates colonic motility by means of gastrocolic reflex in early post-operative patients as it does in healthy population [10] .…”
Section: Discussionmentioning
confidence: 99%